2017
DOI: 10.1186/s13071-017-2372-5
|View full text |Cite
|
Sign up to set email alerts
|

First molecular detection and characterization of zoonotic Bartonella species in fleas infesting domestic animals in Tunisia

Abstract: BackgroundBartonellosis is an emerging vector-borne disease caused by different intracellular bacteria of the genus Bartonella (Rhizobiales: Bartonellaceae) that is transmitted primarily by blood-sucking arthropods such as sandflies, ticks and fleas. In Tunisia, there are no data available identifying the vectors of Bartonella spp. In our research, we used molecular methods to detect and characterize Bartonella species circulating in fleas collected from domestic animals in several of the country’s bioclimatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
2
18
3
Order By: Relevance
“…Our study shows variations in the prevalence of Bartonella in the different hydrographic zones analyzed, and the differences could be associated to both the distribution of flea species and environmental factors. A study conducted on fleas of domestic animals from Tunisia (Zouari et al, 2017) found a higher prevalence of Bartonella in fleas from humid areas, followed by semiarid, sub-humid, and arid regions; this bacterium was not found in the dry zone, contrary to what was found in our study. During our investigation, we found a higher prevalence of the bacterium in arid, semi-arid, and sub-humid zones.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study shows variations in the prevalence of Bartonella in the different hydrographic zones analyzed, and the differences could be associated to both the distribution of flea species and environmental factors. A study conducted on fleas of domestic animals from Tunisia (Zouari et al, 2017) found a higher prevalence of Bartonella in fleas from humid areas, followed by semiarid, sub-humid, and arid regions; this bacterium was not found in the dry zone, contrary to what was found in our study. During our investigation, we found a higher prevalence of the bacterium in arid, semi-arid, and sub-humid zones.…”
Section: Discussioncontrasting
confidence: 99%
“…Although animals included in this study showed relatively high flea infestation, the prevalence of Bartonella in cat fleas seems lower when compared with studies in mainland Spain (Andalucía 11.5%, La Rioja 21.5%) (Márquez et al 2009, Gil et al 2013 and some other Mediterranean countries, such as Israel (64%) or Tunisia (33.4%) (Gutiérrez et al 2015, Zouari et al 2017. Additional investigations covering other islands of the Archipelago might change the prevalence rate.…”
Section: Discussioncontrasting
confidence: 59%
“…After infection, the bacteria eventually enter the erythrocytes and endothelial cells and can persist asymptomatically in a wide range of mammalian reservoir hosts such as rodents, insectivores, carnivores, and ungulates [ 13 15 ]. The infection is transmitted mainly by arthropod vectors including fleas [ 16 ], sand flies [ 17 ], lice [ 18 ], mites [ 19 ] and ticks [ 20 , 21 ]. The transmission and evolution of Bartonella species in mammals is the result of a complex relationship between multiple hosts, vectors and pathogens.…”
Section: Introductionmentioning
confidence: 99%